Approximated area calculation by using discrete least squares method - Rathi, Sidik; Harun, Nurzalina; Hassin, Ain Nur Dania; Sadikin, Zubaidah; Salim Nasir, Mohd Agos (Academica Press Solutions, 2024)
This research delves into the application of the discrete least squares method for approximating the area of Pulau Ketam, an island located in Selangor, Malaysia. The study utilizes 24 data points collected from a detailed map of Pulau Ketam to demonstrate the effectiveness of the method. A user-friendly Graphical User Interface (GUI) named AreaXpert is developed to facilitate the calculation process. The GUI allows users to input coordinates, generate graphs, calculate sums, and ultimately determine the approximated area of the object. By leveraging the power of GUIs and visual aids, this research aims to enhance spatial understanding and support informed decision making in various applications. The findings showcase the potential of the discrete least squares method as a valuable tool for accurate area estimation, paving the way for further advancements in this field.